3D printing and additive manufacturing for customized design : unmanned vehicles - front assembly - Mak, An Nie (2015)
Many industries have been using Additive Manufacturing (AM) technology to increase their efficiency and lower their production cost. Automobile industry is one of the pioneers to do so. AM is mainly used for prototyping in the automobile industry and the prototype is fabricated for functional testing. In this report, the application is scaled down to unmanned vehicle instead of real cars. Radio control car bumper is selected for redesigning and are drawn using SOLIDWORKS, the file formats are compatible with ANSYS. The customize designs of the bumper is simulated using FEA software, ANSYS Explicit Dynamic. The bumpers are simulated to collide with a wall and the solutions obtained are total deformation, (Von-Mises) stress and equivalent strain. These results are compared with a reference bumper, Traxxas Bumper. The selection for the best design is determined using weighted value method and the criteria for evaluation are safety, low cost, performance, producibility and light weight. The selected design is printed using Fused Deposition Modelling (FDM). The printed bumpers are evaluated by examining its dimension accuracy and its surface texture. Practically, the quality of the printed bumpers may not be near to net shape and post processing is still required. This report also provides insights about the advantages of using AM technology and how it will change the way manufacturing industry function in the future by moving towards mass customization.